Strategi Digital Influencer dalam Membentuk Persepsi dan Keputusan Pembelian Konsumen Daviena Skincare - Sormin, Manuela Ruth Claudia; Jenniefer, Jenniefer; Adiarsi, Gracia Rachmi (Jurnal Dinamika Ilmu Komunikasi, 2025)
The development of digital media has reshaped marketing communication, with influencer marketing relying on personal branding and lifestyle representation to influence consumer behavior. A prominent trend is flexing, the display of wealth, luxury, and personal achievements on social media to create exclusivity and aspirational value. In Indonesia’s beauty industry, flexing is widely used, yet little research addresses its effect on consumer perception, trust, and purchase decisions. This study examines Daviena Skincare’s flexing strategy in shaping consumer engagement and decision-making. Using a qualitative approach, in-depth interviews with five purposively selected skincare users and social media followers were analyzed thematically through the AISAS model (Attention, Interest, Search, Action, Share). Results show flexing effectively attracts attention and interest by associating the brand with success and luxury, though responses are ambivalent: some see it as motivational, others as excessive. Long-term trust and purchase depend more on product quality, transparency, and authentic engagement. The study highlights the importance of balancing flexing with authenticity and credibility to build consumer loyalty.